2016
DOI: 10.3390/molecules21111576
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profiling of Flavonoids, Phenolic Acids, Terpenoids, and Volatile Fraction of a Rosemary (Rosmarinus officinalis L.) Extract

Abstract: This paper presents a comprehensive analysis of the phytochemical profile of a proprietary rosemary (Rosmarinus officinalis L.) extract rich in carnosic acid. A characterization of the (poly)phenolic and volatile fractions of the extract was carried out using mass spectrometric techniques. The (poly)phenolic composition was assessed by ultra-high performance liquid chromatography-electrospray ionization-mass spectrometry (UHPLC-ESI-MS n ) and a total of 57 compounds were tentatively identified and quantified, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
103
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(134 citation statements)
references
References 59 publications
(89 reference statements)
11
103
0
Order By: Relevance
“…However, different composition of this Jordanian cultivated oil of Rosmarinus officinalis L. (Lamiaceae) by these phenolic compounds may give unique antioxidant activity. The essential oil and RE composition of these phenolic compounds (mono or di-terpenes) has been reported in a variable % which associated with several other factors such as genetic, storage condition, extraction method (Mena et al, 2016). On addition, it was reported in several study that the level of using RE or their essential oil in the food need more investigation (Kahraman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, different composition of this Jordanian cultivated oil of Rosmarinus officinalis L. (Lamiaceae) by these phenolic compounds may give unique antioxidant activity. The essential oil and RE composition of these phenolic compounds (mono or di-terpenes) has been reported in a variable % which associated with several other factors such as genetic, storage condition, extraction method (Mena et al, 2016). On addition, it was reported in several study that the level of using RE or their essential oil in the food need more investigation (Kahraman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…1) that has been identified as the major bioactive phytochemical in numerous medicinal plants, including Rosmarinus officinalis (8), Salvia fruticosa (9) and Ocimum sanctum (10). Previous pharmacological studies have demonstrated that carnosic acid affords various biological activities, such as neuroprotection (11), prevention of advanced glycation end-product formation (12), attenuation of Alzheimer's disease (13), anticancer activity (14), anti-inflammation (15) and renoprotection (16).…”
Section: Introductionmentioning
confidence: 99%
“…TFC-mg of RU/g of dry hydro methanolic extract. Terminalia species of Combretaceae contains the highest flavonoid content compared to Anogeissus species and combretum albidum ( In a recent study, Flavonoid compounds have been isolated characterized by ultra-high performance liquid chromatographyelectrospray ionization-mass spectrometry (UHPLC-ESI-MS) [15]. Flavonoid has been used as chemotaxonomic markers in the genus Drosera [16].…”
Section: Resultsmentioning
confidence: 99%